2017
DOI: 10.1108/ajar-2017-02-02-b005
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Expectation Gap between Independent Auditors and Users from Auditing Services Related to the Quality of Auditing Services Based on Their Role and Professional Features

Abstract: In this research, using an analytical framework on factors affecting the quality of auditing services, we consider factors that affect an expectations gap in providers and users of auditing services related to factors affecting auditing quality. Effective factors studied in this regard are professional features, including the professional role of individuals in the auditing process (auditors against preparers of financial statements), professional experience of individuals, professional rating and size of audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…First, it shows that there are no overall financial statement level (OFSL) threats and users can feel confident in using these financial statements to make informed financial decision. In other words, the findings reduced OFSL risk, that is, the risk of material misstatement for the financial statement as a whole (see also Behzadian and Izadi Nia, 2017). Second, and partly synonymous with the first, is that the results directly enhance the relevance and reliability of information provided in the financial statements for strategic investment decision making.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…First, it shows that there are no overall financial statement level (OFSL) threats and users can feel confident in using these financial statements to make informed financial decision. In other words, the findings reduced OFSL risk, that is, the risk of material misstatement for the financial statement as a whole (see also Behzadian and Izadi Nia, 2017). Second, and partly synonymous with the first, is that the results directly enhance the relevance and reliability of information provided in the financial statements for strategic investment decision making.…”
Section: Resultsmentioning
confidence: 97%
“…see Fanning and Cogger, 1998; Lyandres and Zhdanov, 2013). These findings provide meaningful insights to financial institutions when determining lending decisions and to investors when evaluating companies’ financials to make investment decisions (Bell and Carcello, 2000; Beneish et al , 2013; Behzadian and Izadi Nia, 2017; Lokanan, 2017).…”
Section: Conclusion Limitations and Areas For Future Researchmentioning
confidence: 90%
See 2 more Smart Citations
“…They found that performance audit growth has continued but not always consistently over time and across audit jurisdictions. Fatah and Naser (2017) found that role of professionals in the auditing process is not effective as an independent auditor or financial statements provider, as well as the professional experience of individuals in the expectations gap from factors affecting auditing quality, while the size and qualities of the auditing firms were influenced by the expectations gap of individuals in the field of auditing regulation. Based on the literature review of the study it can be seen that there are lack of research in this particular study.…”
Section: Research Objectivesmentioning
confidence: 97%